2022
DOI: 10.2147/jpr.s346242
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Study on Acupuncture Inhibiting Inflammation and Bone Destruction in Knee Osteoarthritis Induced by Monosodium Iodoacetate in Rat Model

Abstract: We aim to explore whether acupuncture inhibits inflammation and bone destruction in rat model monosodium iodoacetate (MIA)-induced knee osteoarthritis (KOA) by 18Ffluorodeoxyglucose (18F-FDG) small-animal positron emission tomography (PET) and micro-computed tomography (CT) imaging. Methods: KOA was induced in rats by intra-articular injection MIA (2 mg/50 μL) through the right knee of the rats. Forty male Sprague Dawley rats weighing 280 to 340 g (12 weeks old) were randomly divided into four groups including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A study showed that after injection of mifepristone into the knee joint of rats, there was obvious bone destruction in KOA model rats, the number and joint density of subchondral bone trabeculae decreased, and the bone trabeculae were sparse and disorderly distributed, while the bone destruction was significantly improved after acupuncture treatment, demonstrating that acupuncture can inhibit the development of osteophytes and subchondral bone remodeling. 82 …”
Section: Effect Of Traditional Chinese Non-pharmacological Therapies ...mentioning
confidence: 99%
See 2 more Smart Citations
“…A study showed that after injection of mifepristone into the knee joint of rats, there was obvious bone destruction in KOA model rats, the number and joint density of subchondral bone trabeculae decreased, and the bone trabeculae were sparse and disorderly distributed, while the bone destruction was significantly improved after acupuncture treatment, demonstrating that acupuncture can inhibit the development of osteophytes and subchondral bone remodeling. 82 …”
Section: Effect Of Traditional Chinese Non-pharmacological Therapies ...mentioning
confidence: 99%
“…In addition, oxidative stress caused by the accumulation of reactive oxygen species (ROS) is also a key factor leading to chondrocyte apoptosis. 44 WNA can inhibit oxidative stress in cartilage of sodium iodoacetate induced KOA model rats, 45 mainly by reducing the expression of malondialdehyde (MDA) and NADPH-oxidase (NOX2) in cartilage tissue, and increasing the expression of superoxide dismutase 2 (SOD2). MDA is a marker used to reflect the degree of oxidative stress damage, 46 and NOX2 is one of the main enzymes that promote ROS production and participate in the oxidation process.…”
Section: Inhibiting Chondrocyte Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the effects and mechanisms of acupuncture, further studies with larger sample sizes and long-term acupuncture treatments are needed. In addition, studies have shown that acupuncture can delay cartilage degeneration [35] and reduce inflammation and bone destruction [36], whereas electroacupuncture can delay cartilage degeneration and prevent cellular changes [37]. However, studies on cartilage degeneration and regeneration have been conducted on animals, with only few clinical studies being conducted on humans, and future research should thus involve clinical trials on acupuncture.…”
Section: Keyword Analysismentioning
confidence: 99%
“…It has been reported that inflammation serves a key role in the pathogenesis of KOA (1,(9)(10)(11)(12). The activation of the NOD-like receptor protein 3 (NLRP3) inflammasome initiates the inflammatory cascade, and it is closely related to a number of types of chronic inflammation (13).…”
Section: Introductionmentioning
confidence: 99%